Clash of Civilisations: Hambatan Aksesi Turki ke Uni Eropa - Rahim, Faidah (Global and Policy Journal of International Relations, 2013)
ABSTRACTTurkey’s accession to European Union has been taking a long time. Turkey had applied for full European Economic Community membership in 1987. In Helsinksi Summit 1999, European Union advanced Turkey’s status as candidate country. Since then, Turkey keeps on attempting to fulfill the Copenhagen Criteria required to open the accession negotiation. Turkey and European Union finally started the negotiation in 2005. But in the progress, the negotiation process between Turkey and European Union has been very slowly. Turkey is still faced to some problems such as human rights and its conflict with Cyprus. Some state members explicitly show their oppositions to Tukey’s full membership. The oppositions are mainly based on the Turkey’s cultural, historical, and identity difference as a state with predominantly Muslim. This article is focused on cultural and identity factor to analyse the indication of clash of civilisations in European Union’s relation with Turkey. This clash of civilisations will be one of the factors that inhibits Turkey’s accession to European Union.Keywords: Turkey’s accession, European Union, Clash of civilisationsDOI:https://doi.org/10.33005/jgp.v1i02.2000